Does the 2008-global financial crisis matter for the determinants of conventional and Islamic banking performances in Indonesia? - M. Shabri Abd. Majid; Sri Ulina (Faculty of Economics, Universitas Islam Indonesia, 2020)
Purpose – This study explores comparatively the effects of capital adequacy, non-performing loans/financing, liquidity, and operating expenses on Indonesia’s conventional and Islamic banking performances between the pre-and post-2008 Global Financial Crisis (GFC) periods.Methodology – The study selected the three respective largest conventional and Islamic banks as a sample of the study using a purposive sampling technique. The data for the pre-2008 GFC period (i.e., 2003 – 2008) and the post-2008 GFC period (i.e., 2009 – 2017) were analyzed using a panel multiple regression analysis.Findings – The study documented different influences of capital adequacy, liquidity, non-performing loans/financing, and operating expenses on conventional and Islamic banking performances between the pre- and post-2008 GFC. Research limitations – This study only investigated the banks’ characteristics as the determinants of banking performances and compared merely the effects the pre- and post-2008 GFC periods.Practical implications – To maintain and enhance their performances, the Islamic and conventional banks should adopt different financial policies between the normal and turbulent economic periods. The Islamic banks were in a better position amid the crisis, showing an urgent need for the government to further promote Islamic banks, as they could offer better solutions for economic stability.Originality – The study examined a larger number of conventional and Islamic banks over more extended and updated study periods, namely six years (i.e., 2003-2008) before the 2008 GFC and ten years (i.e., 2009-2018) after the 2018 GFC. The study is among the first attempts to comparatively analyze the determinants of Indonesia’s Islamic and conventional banking performances between the pre- and post-2008 GFC periods using the panel multiple regression analysis to arrive at more comprehensive and robust empirical evidence.